You are on page 1of 1

Proof of the Jacobi Identity

First, we establish a relationship for later use: Let f, g be functions f, g ∈ {u, v, w} with f 6≡ g and a ∈ {p1 , ..., pN , q1 , ..., qN }
such that f and g depend partially on a.
N  
∂ ∂ X ∂f ∂g ∂f ∂g
{f, g} = −
∂a ∂a i=1 ∂qi ∂pi ∂pi ∂qi
N
∂2f ∂ g ∂ f ∂2g ∂2f ∂ g ∂ f ∂2g
X  
= + − −
i=1
∂a∂qi ∂pi ∂qi ∂a∂pi ∂a∂pi ∂qi ∂pi ∂a∂qi
   
∂f ∂g
= , g + f, (†)
∂a ∂a
Now we can prove the Jacobi identity:
J = {u, {v, w}} + {v, {w, u}} + {w, {u, v}}

expand the last term...


( N
)
X ∂u ∂v ∂u ∂v
= {u, {v, w}} + {v, {w, u}} + w, −
i=1
∂qi ∂pi ∂pi ∂qi

by linearity...
N    
X ∂u ∂v ∂u ∂v
= {u, {v, w}} + {v, {w, u}} + w, − w,
i=1
∂qi ∂pi ∂pi ∂qi

by the product rule...


N         
X ∂u ∂v ∂v ∂u ∂u ∂v ∂v ∂u
= {u, {v, w}} + {v, {w, u}} + w, + w, − w, − w,
i=1
∂qi ∂pi ∂pi ∂qi ∂pi ∂qi ∂qi ∂pi

by †
    
N     
 ∂u
 ∂ ∂w  ∂v
X  ∂ ∂w
= {u, {v, w}} + {v, {w, u}} + {w, v} − ,v  + {w, u} − ,u 
  
 ∂qi  ∂pi ∂pi  ∂pi  ∂qi ∂qi
  
i=1

| {z } | {z }
A B
   
   
∂u  ∂ ∂w  ∂v
 ∂ ∂w
− {w, v} − ,v  − {w, u} − , u 
  
∂pi  ∂qi ∂qi  ∂qi  ∂pi ∂pi
 

| {z } | {z }
A B

grouping terms A and terms B...


A B
N         
 
z }| { z }| { X
  ∂u ∂w ∂v ∂w ∂u ∂w ∂v ∂w
{u,{v,
= {v,{w,
 w}} + 
  u}} − 
 {u,{v,
 w}} − 
 {v,{w,
 u}} + − ,v − ,u + ,v + ,u
i=1
∂qi ∂pi ∂pi ∂qi ∂pi ∂qi ∂qi ∂pi

expanding these remaining terms...


N N N N
X ∂ u ∂2w ∂ v X ∂ u ∂2w ∂ v X ∂ v ∂2w ∂ u X ∂ v ∂2w ∂ u
=− + − +
i,j=1
∂qi ∂pi ∂qj ∂pj i,j=1 ∂qi ∂pi ∂pj ∂qj i,j=1 ∂pi ∂qi ∂qj ∂pj i,j=1 ∂pi ∂qi ∂pj ∂qj
| {z } | {z } | {z } | {z }
C D E C
N N N N
X ∂ u ∂2w ∂ v X ∂ u ∂2w ∂ v X ∂ v ∂2w ∂ u X ∂ v ∂2w ∂ u
+ − + −
i,j=1
∂pi ∂qi ∂qj ∂pj i,j=1 ∂pi ∂qi ∂pj ∂qj i,j=1 ∂qi ∂pi ∂qj ∂pj i,j=1 ∂qi ∂pi ∂pj ∂qj
| {z } | {z } | {z } | {z }
E F F D

We note that since each term is summed over all i, j, then each term is symmetric in i, j. Hence each pair of terms C, D, E, F
cancels and we get
J ≡0

Rowan Lonsdale